Comparative histology of embryogenic cell and somatic embryo initiation in callus cultures of mungbean [Vigna radiata (L.) Wilczek], pole sitao [V. unguiculata (L.) Walp. var. sesquipedalis (L.) Koern.] and mothbean [V. aconitifolia (Jacq.) Marechal] - Quimado, Marilyn O. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
Histological examinations of cotyledon- and leaf-derived callus cultures of mungbean (Vigna radiata L. Wilczek), pole sitao (V. unguiculata L. Walp. var. sesquipedalis L. Koern., and mothbean (V. aconitifolia Jacq. Marechal) initiated using MS-B5 medium with three different auxins were done to determine the origin and development of embryogenic cells and somatic embryos. This was aimed at explaining the inherent difficulty in effecting plant regeneration by somatic embryogenesis from callus cultures in the genus Vigna. Five-d-old cotyledons of pole sitao cv. UPL PS2 and mungbean cv. Pag-asa 3 inoculated in 20 mg L-1 2,4-D, and of pole sitao cv. UPL PS2 and mungbean cv. Pag-asa 7 grown in 10 mg L-1 dicamba formed cambium-like zone due to active division of perivascular cells. This was also observed in leaf sections of pole sitao cv. UPL PS1 cultured in 20 mg L-1 2,4-D and 10 mg L -1 picloram, and from established callus cultures of mothbean maintained in 2 mg L-1 2,4-D and 0.5 mg L-1 BAP. The presence of the cambium-like zones resulted in the formation of globular proembryoids from meristematic mass of cells. A small number of somatic embryo originating from single cell resembling zygotic embryo in origin and morphology was observed in pole sitao cv. UPL PS1 inoculated in 10 mg L-1 picloram. The proembryonic structures and somatic embryos in mungbean and pole sitao were not observed to differentiate into more advanced stage as evidenced by the absence of the meristemoids in 3- and 4-wk-old cultures. On the other hand, various advanced stages of somatic embryogenesis originating from mass of cells were observed in established callus cultures of mothbean aces. 3374 and 3381. In addition, clumps of embryogenic individual cells at different stages were noted within the same explant in ace. 3381. Various modifications on the tissue culture medium and conditions are recommended to enhance the proliferation of meristemoids, allow subsequent differentiation of the proembryoids and eventually achieve regeneration in the recalcitrant mungbean and pole sitao.